The connectedness of the solutions set for generalized vector equilibrium problems. (1st February 2016) - Han, Yu; Huang, Nan-jing
Abstract : In this paper, we establish the connectedness of the sets of Henig efficient solutions, globally efficient solutions, weak efficient solutions, superefficient solutions and efficient solutions for a class of generalized vector equilibrium problems without the assumptions of monotonicity and compactness.